2012
DOI: 10.1159/000337573
|View full text |Cite
|
Sign up to set email alerts
|

Same-Day Discharge in Clinical Stage I Endometrial Cancer Patients Treated with Total Laparoscopic Hysterectomy, Bilateral Salpingo-Oophorectomy and Bilateral Pelvic Lymphadenectomy

Abstract: Objectives: The purpose of this retrospective study was to evaluate the capacity for same-day discharge in clinical stage I endometrial cancer (EC) patients treated with total laparoscopic hysterectomy (TLH), bilateral salpingo-oophorectomy (BSO) and bilateral pelvic lymph node dissection (BPLND). Methods: We retrospectively reviewed the charts ofstage I EC patients who were treated with TLH, BSO and BPLND and discharged on the same day. The intra- and postoperative clinical variables (e.g., age, complications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Of the six prospective studies retrieved, four examined total laparoscopic hysterectomy, one included robotic‐assisted laparoscopic hysterectomy, and one included laparoscopic supra‐cervical hysterectomy. Among the nine retrospective studies, five included two or three procedures: total laparoscopic hysterectomy and robotic‐assisted laparoscopic hysterectomy (two studies), total laparoscopic hysterectomy and laparoscopic supra‐cervical hysterectomy (two studies), and total laparoscopic hysterectomy, laparoscopically assisted vaginal hysterectomy, and laparoscopic supra‐cervical hysterectomy (one study); three studies included robotic‐assisted laparoscopic hysterectomy only; and one study included total laparoscopic hysterectomy only (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Of the six prospective studies retrieved, four examined total laparoscopic hysterectomy, one included robotic‐assisted laparoscopic hysterectomy, and one included laparoscopic supra‐cervical hysterectomy. Among the nine retrospective studies, five included two or three procedures: total laparoscopic hysterectomy and robotic‐assisted laparoscopic hysterectomy (two studies), total laparoscopic hysterectomy and laparoscopic supra‐cervical hysterectomy (two studies), and total laparoscopic hysterectomy, laparoscopically assisted vaginal hysterectomy, and laparoscopic supra‐cervical hysterectomy (one study); three studies included robotic‐assisted laparoscopic hysterectomy only; and one study included total laparoscopic hysterectomy only (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…In our study, the complication rate was 0.9 %. In various studies conducted, Karaman et al [15] and Brummer et al [7] described a major complication rate of 1 and 1.8 %, respectively. In addition, Donnez described his retrospective study with 400 patients who underwent laparoscopic hysterectomy procedure, a major complication rate of 1.5 % [14].…”
Section: Discussionmentioning
confidence: 99%
“…Later gynecologic surgeons have made many efforts to improve the technique thereby shortening the learning curve and improve outcomes, reducing iatrogenic urinary-tract injuries, intraoperative blood loss [4], hospitalization time, and recovery time [5]. Now with the improvement of surgical skills, it has been considered with a day surgery hospital stay [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…20 Rettenmaier and colleagues reported a series of 21 patients who were discharged home on the day of total laparoscopic hysterectomy with bilateral salpingooophorectomy and bilateral PLND dissection for endometrial cancer, and noted acceptable complication rates, concluding that SDD is feasible in the laparoscopic management of endometrial cancer. 19 More recently, Penner and colleagues found that SDD was feasible and safe in a series of 141 patients undergoing comprehensive staging for endometrial or cervical cancer. 21 Among 200 patients scheduled for robotic-assisted laparoscopic hysterectomy for a mixture of benign and malignant indications, Lee and colleagues found that 78 % of patients could be discharged home on the day of surgery, with acceptable rates of urgent care visits and readmission.…”
Section: Discussionmentioning
confidence: 99%
“…Several retrospective studies have suggested that despite older age and higher rates of comorbidities, perioperative morbidity and readmission rates after SDD are acceptably low in patients undergoing laparoscopic management of gynecologic cancers. [19][20][21][22] Gynecologic oncologists in our institution began implementing SDD for patients undergoing laparoscopic hysterectomy for endometrial cancer and EIN in 2011. In collaboration with a dedicated anesthesiologist, perioperative care protocols favoring SDD were developed, resulting in the broad adoption of SDD for patients undergoing laparoscopic management of these conditions.…”
mentioning
confidence: 99%